2017
DOI: 10.1002/cjce.23000
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of spherical structured catalysts by dip‐coating: Application to n‐butane dehydrogenation

Abstract: This work analyzes the deposition conditions of thin layers of γ‐Al2O3 by dip‐coating on a spherical substrate of α‐Al2O3 spheres. Results showed that under controlled deposition conditions, a structured support of α‐Al2O3 spheres coated by a uniform γ‐Al2O3 layer (thickness ≈ 15 µm) of good adherence can be attained. Optimal preparation conditions for the coating, that involved pretreatment of the substrate, gel formation, deposition conditions, and thermal treatments, were obtained. Pt catalysts supported on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…[47,48] Other studies developed structured supports by coating of γ-Al 2 O 3 in compact spheres and studied Pt, PtSn, and PtGe catalysts for the n-butane and n-decane dehydrogenation reactions. [49][50][51] On the other hand, there are works that study the coating with MgAl 2 O 4 on metallic foams, micromonoliths of FeCrAl alloys, and honeycomb cordierite ceramics, used in the synthesis of Ni, Ru-Ni, and Pt catalysts for steam reforming, CO 2 metanation, and hydrogen combustion. [12,[52][53][54] Also, there is vast bibliography on structured catalysts supported on foams and other monoliths coated with different materials such as La-Ni/Al 2 O 3 on cordierite monoliths, CeO 2 -NiO-Al 2 O 3 /Ni-foam, CeO 2 -ZrO 2 -modified NiO-Al 2 O 3 /Ni-foam, and MoVTeNbO supported on SiC foam applied to oxidative dehydrogenation of paraffins.…”
Section: Introductionmentioning
confidence: 99%
“…[47,48] Other studies developed structured supports by coating of γ-Al 2 O 3 in compact spheres and studied Pt, PtSn, and PtGe catalysts for the n-butane and n-decane dehydrogenation reactions. [49][50][51] On the other hand, there are works that study the coating with MgAl 2 O 4 on metallic foams, micromonoliths of FeCrAl alloys, and honeycomb cordierite ceramics, used in the synthesis of Ni, Ru-Ni, and Pt catalysts for steam reforming, CO 2 metanation, and hydrogen combustion. [12,[52][53][54] Also, there is vast bibliography on structured catalysts supported on foams and other monoliths coated with different materials such as La-Ni/Al 2 O 3 on cordierite monoliths, CeO 2 -NiO-Al 2 O 3 /Ni-foam, CeO 2 -ZrO 2 -modified NiO-Al 2 O 3 /Ni-foam, and MoVTeNbO supported on SiC foam applied to oxidative dehydrogenation of paraffins.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, 2-propanol conversion tests (to evaluate the acidity of the supports) showed that γ-Al 2 O 3 has a higher acid character than MgAl 2 O 4 . 33,46 Nevertheless, the acidity of alumina is not enough to catalyze cyclization reactions in the citral hydrogenation. 33…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, 2-propanol conversion tests (to evaluate the acidity of the supports) showed that γ-Al 2 O 3 has a higher acid character than MgAl 2 O 4 . 33,46 Nevertheless, the acidity of alumina is not enough to catalyze cyclization reactions in the citral hydrogenation. 33 The results of the test reactions are presented in Table 2: initial reaction rate (R 0 CH ) and activation energy (E a CH ) values for the cyclohexane dehydrogenation (CHD), the initial reaction rate (R 0 CP ) for the cyclopentane hydrogenolysis (CPH).…”
Section: Catalysts Characterization Resultsmentioning
confidence: 99%
See 1 more Smart Citation